Near-infrared spectroscopy and hidden graphics applied in printing security documents in the offset technique - Žiljak, Vilko (Array, 2019)
The method of mixing pigments for the printing technology is expanded with the addition of dual states in security graphics. Near-infrared spectroscopy of colorants used in the offset technique has brought about the concept of targeted design by a selective use of colorants that are visible in the visible region of the electromagnetic spectrum. High-security documents have been observed in the NIR light based on twin colorants which are differentiated according to their NIR absorption in the range from 800 to 1000 nm. New procedures have been developed based on the innovative creation of documents with hidden information. Two graphics are combined with mutating screen elements. A mathematical definition of the new printing screen and an algorithm in PostScript are given. The designer plans and creates graphics, which originate from the twin colorants, by using the INFRAREDESIGN® method. The dual design was investigated using visual and infrared cameras for the forensic area. The components of colorants are determined by the spectroscopy of light absorption with filters in the visual and NIR spectrum.